Colour Measurement by UV Absorption Technique - N., Baharudin; Nor Mazlee, Norazmi; Hadi, Manap (IJIRR, 2017)
The aim of this research work was to acquire and classify different colour scales resulted by serial dilutions of a specific colour. Through the serial dilutions, different colour scales were obtained and analyzed for a dialysis purpose. Visible (VIS) light spectrometer was proposed to measure the colour absorption through the integration with Spectrasuite software which respects to absorption. Spectrasuite is able to display spectral patterns corresponding to the absorption. Each colour scale indicates a different concentration. Thus, spectrometer was proved to distinguish different colour scales and it must even overcome cross-sensitivity issue. The application was validated through a correlation with the use of International Commission on Illumination (CIE) spectral measurement system. Every colour scale was successfully classified by a standard colour code. Thus, the spectrometer is applicable for the colour measurement analysis by absorption method besides contributing benefits to various applications.